Efektifitas Perasan Kulit Mangis Sebagai Pengganti Eosin 2% Pada Pemeriksaan Telur Cacing - Febriyanti, Eka; Mulia, Putra; Valencia, Trivini (UPT Laboratorium Terpadu, Universitas Diponegoro, 2024)
Examination of Intestinal Nematode worm eggs is one of the practicum subjects in the Basic Science of Nursing course at the Biomedical Laboratory of the Faculty of Nursing, University of Riau. Eosin 2% is a stain used in the examination of Intestinal Nematode worm eggs. However, the availability of 2% eosin cannot be sufficient to facilitate every student. This is because the procurement of consumables in the laboratory is very limited. An alternative new coloring method is needed using natural ingredients, one of which is derived from mangosteen peel juice. This study aims to determine the effectiveness of the percentage of mangosteen peel juice that can be used as a substitute for 2% eosin. The research design was an experimental study using a completely randomized design (CRD). The subjects of the study were direct staining of mangosteen peel juice and 2% eosin as a control. The object of research is worm positive feces. As a treatment is mangosteen peel which consists of 2 (two) times the level of treatment, namely mangosteen peel juice 5%, 10%. The results showed that a concentration of 10% mangosteen peel juice was effective in examining worm eggs as a substitute for eosin. Based on the results obtained, it can be concluded that mangosteen peel juice is effective as a substitute for 2% eosin in staining worm eggs, namely at a concentration of 10%.